Measurement and valuation of health providers' time for the management of childhood pneumonia in rural Malawi: an empirical study. Issue 1 (December 2016) - Bozzani, Fiammetta; Arnold, Matthias; Colbourn, Timothy; Lufesi, Norman; Nambiar, Bejoy; Masache, Gibson; Skordis-Worrall, Jolene
Abstract Background Human resources are a major cost driver in childhood pneumonia case management. Introduction of 13-valent pneumococcal conjugate vaccine (PCV-13) in Malawi can lead to savings on staff time and salaries due to reductions in pneumonia cases requiring admission. Reliable estimates of human resource costs are vital for use in economic evaluations of PCV-13 introduction. Methods Twenty-eight severe and twenty-four very severe pneumonia inpatients under the age of five were tracked from admission to discharge by paediatric ward staff using self-administered timesheets at Mchinji District Hospital between June and August 2012. All activities performed and the time spent on each activity were recorded. A monetary value was assigned to the time by allocating a corresponding percentage of the health workers' salary. All costs are reported in 2012 US$. Results A total of 1, 017 entries, grouped according to 22 different activity labels, were recorded during the observation period. On average, 99 min (standard deviation, SD = 46) were spent on each admission: 93 (SD = 38) for severe and 106 (SD = 55) for very severe cases. Approximately 40 % of activities involved monitoring and stabilization, including administering non-drug therapies such as oxygen. A further 35 % of the time was spent on injecting antibiotics. Nurses provided 60 % of the total time spent on pneumonia admissions, clinicians 25 % and support staff 15 %. Human resource costs were approximately US$ 2 per bed-day and, on average, US$ 29.5 per severe pneumonia admission and US$ 37.7 per very severe admission. Conclusions Self-reporting was successfully used in this context to generate reliable estimates of human resource time and costs of childhood pneumonia treatment. Assuming vaccine efficacy of 41 % and 90 % coverage, PCV-13 introduction in Malawi can save over US$ 2 million per year in staff costs alone.